Dėl Latgalės „giliųjų šnektų“ daugiskaitos kilmininko su -ūs kilmės - Rosinas, Albertas (Baltistica, 1997)
ON THE ORIGIN OF THE GENITIVE PLURAL -ūs IN LATGALE ‘DEEP’ SUBDIALECTSThe problem of the origin of the genitive plural -ūs in Latgale ‘deep’ subdialects had already been investigated by J. Endzelīns, V. Mažiulis and A. Rosinas. Recently, the origin of the said ending has been attempted to establish by A. Breidaks as well. In his opinion, the genitive plural ending of pronominal adjectives and such anaphoric pronouns as tas, šis, jis, viņš is a phonetically modified relic of the Proto-Indo-European genitive dual *-ōs, i.e. Ide. *-ōs > East Balt. *-ōs > Latv. -u˚ > -ūs.The reconstruction of the Indo-European dual ending itself is hardly plausible, either (cf. Szemerényi et al.). V. Mažiulis, who has investigated the problem, came to the conclusion that the Indo-Europeans had never possessed such a dual ending. He maintains that in Proto-Baltic the o-stem genitive-‘locative’ form was *-au (Ide. *-ou) which acquired the formant -s from the hypothetical locative plural *(t)uos
Keywords: kilmininkas; latvių kalba; Latgalė